Workplace violence against healthcare workers in Emergency Departments. A case-control study: Workplace violence in Emergency Departments - d'Ettorre, Gabriele; Vullo, Annamaria (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Assessment and management of workplace violence (WPV) towards healthcare workers (HCWs) employed in Emergency Departments (EDs) represents a challenge for healthcare organizations worldwide. To date there is a lack of scientific data about the impact of work-shifts on the occurrence of WPV against ED HCWs. The purpose of this study was to investigate the relationship between work shift schedules and WPV against registered nurses (RNs) working on non-traditional shifts, including nights and 12-hour shifts. Methods: The authors conducted a cross-sectional nested case-control analysis of data regarding the episodes of WPV perpetrated by patients or their relatives against RNs employed in three EDs, in the period between January –December 2017. Results: The one-year incidence of WPV was 29,30 per 100 Full Time Equivalent (FTE) positions. Cumulative nightshifts were significant for 3 or more nightshifts compared to working less than 3 nightshifts during the 7 days before the episodes of WPV; additionally, RNs working 9 or more night-shifts showed higher risk of experiencing WPV compared to RNs working less than 4 night-shifts in the previous 28 days. Conclusion: In the present study shift work and WPV occurrence against ED RNs resulted interconnected; improvement interventions aimed at preventing the WPV should consider the characteristics of work shift schedules with the purposes of: 1) limiting the night shifts up to two per week and up eight per month; 2) adopting constant forward-rotating shift schedules. (www.actabiomedica.it)